Manajemen Sarana dan Prasarana Pendidikan di Pondok Pesantren Darul Aufa Kabupaten Batanghari - Khalik Khalik; Fadlilah; Nur Ainun Siregar (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to determine the planning, procurement, maintenance and utilization of existing facilities and infrastructure at the Darul Aufa Muara Bulian Islamic Boarding School.This research uses a descriptive qualitative approach, the source of data obtained is from the Leadership, Waka Sarpras, and Students. The results showed that 1) the planning carried out at the Darul Aufa Islamic Boarding School was carried out at the beginning of each year, 2) the procurement carried out, namely receiving grants, buying, and making their own. 3) maintenance carried out, namely maintaining together and the existence of a list of pickets to take care of every day 4) utilization at this Islamic Boarding School is used which one is there first, then that is what will be used.